The fate of the self-speaking, according to imagine philosophers of the Arab-Islamic civilization - Mahlobi, Borhan (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research focus on the failure project to reconcile philosophy and religion in the Arab-Muslim medieval society through a review of what the philosophers of this society in the cause of human fate after the paradox of self to her body worldly. This case is as the issue of God’s relationship with the world and the theory of prophecy and the theory emanation. All these issues were sharp philosophical contentious issues between the owners of the project in the face of official religious text. In addition: This research is an attempt to exclude philosophy for ideological affiliations to become this research biased to the term philosophy in the Arab-Muslim cultural society instead of Arabic or Islamic philosophy.